Macroeconomic fluctuations in a New Keynesian disequilibrium model - Bas van Aarle (Journal of Economic Structures, 2017)
This study extends the current New Keynesian modeling framework by changing one crucial aspect: it replaces the general equilibrium assumption by the arguably more realistic assumption of macroeconomic disequilibrium. As a result, more complex and less smooth macroeconomic adjustment dynamics result, as it is not necessary to assume that goods and labor markets continuously clear. The disequilibrium dynamics in the form of regime-dependent output-, employment-, price- and wage fluctuations complicate the decision making problems faced by the fiscal and monetary policy makers substantially. In particular, the possibility of (multiple) regime switches implies the need for deeper analysis and careful monitoring of the disequilibrium mechanisms and dynamics when designing and implementing monetary and fiscal policies.
Keywords: C22; E32; E66; F42; 330; Disequilibrium analysis; New Keynesian model; Rationing; Macroeconomic policy